2011
DOI: 10.1007/s12648-011-0150-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of daily total column ozone (TCO) and role of its depletion and formation rate on surface temperature over Dumdum at Kolkata, India

Abstract: The purpose of the paper is to present the variation of total ozone concentration over Dumdum at Kolkata, India during different seasons. It is concluded that the trend of ozone concentration during different seasons are different. A critical analysis is done and following important results are obtained. (i)The total ozone concentration increases during the pre-monsoon and winter periods. During premonsoon period rate of formation of ozone increases sharply with the rise of surface temperature.(ii) TCO decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Stations over Southern Peninsula and over the lower Ganga valley had been found to exhibit at decreasing trend at same level of significance. The studies of ozone layer is different parts of the world have been reported [8][9][10][11] Monod and Carlier [12] performed a box model study of the multiphase photochemistry (both gas and aqueous phases) of C 1 organic compounds within a non-precipitating cloud on a local scale. They found that in a situation where ozone accumulates in clear sky conditions, as soon as cloud is formed, the tropospheric ozone estimate changes drastically; the net production decreases by a factor of 2 or more and depending on the NOx concentration and the pH values, can actually lead to chemical destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Stations over Southern Peninsula and over the lower Ganga valley had been found to exhibit at decreasing trend at same level of significance. The studies of ozone layer is different parts of the world have been reported [8][9][10][11] Monod and Carlier [12] performed a box model study of the multiphase photochemistry (both gas and aqueous phases) of C 1 organic compounds within a non-precipitating cloud on a local scale. They found that in a situation where ozone accumulates in clear sky conditions, as soon as cloud is formed, the tropospheric ozone estimate changes drastically; the net production decreases by a factor of 2 or more and depending on the NOx concentration and the pH values, can actually lead to chemical destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone can be used for bacterial sterilization [16], purifying drinking water systems instead of the chlorine [17] with the advantage of ozone does not form organo-chlorine compounds, and does not remain in the water after treatment, once it has decayed; it leaves no taste or odor in drinking water. It has diverse effect in atmosphere [18][19][20].…”
Section: N N Morgan a Metawa And A Garamoonmentioning
confidence: 99%
“…It is greatly influenced by predominant meteorological conditions (temperature, solar flux, wind speed and relative humidity). Several authors have studied the possible interaction of surface temperature and cloud cover on ozone concentration (Liu et al 2006 ; Voulgarakis et al 2009 ; Jana et al 2010 , 2011 ; Midya et al 2011 ; Ghosh et al 2015 ). O 3 concentration increases with an increase in solar flux and temperature (Gorai et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%